Nineteenth-century religion and literature: an introduction - Knight, Mark (Oxford University Press, 2006)
An ambitious book...an important work which will no doubt stimulate much reflection and debate...a sturdily bound, well-indexed text. - William Baker, Modern Language Review;Knight and Mason capture the flavour of each individual text beautifully, serving to tantalise and encourage further reading rather than to frustrate, and their analysis is scholarly and suggestive. Although it is extremely selective, this is an excellent introduction to a broad and complex subject, and will provide interested readers with a solid starting point. - Kate Harper, University of York;This text provides an acce